Aplicação de metodologia de avaliação superficial de pavimento: estudo de caso em trecho da RN-177 - Cavalcante, Augusto César Chaves (Universidade Federal Rural do Semi-Árido, 2017)
This work presents a theoretical and empirical discussion about Pavement Management, analyzing the evaluation methodology of the condition of flexible asphalt pavements, showing the numerous types of defects that may arise in them, also indicating their extent and their level of severity. The main objective of the study was to characterize the traffic conditions of a extent of the RN-177, identifying the existing defects, through obtaining the Pavement Condition Index - PCI, developed by the United States Army Corps of Engineers – USACE. The methodology used was based on field survey methods, extracted from the SHRP manual for defect identification, and on quantitative analyzes based on the USACE methodology. It was verified the occurrence of defects in the extension of the sections of the analyzed section, referring to potholes, longitudinal cracks, patches, wear, exudation, permanent deformation in wheel track and slope between road and roadway. The results allowed the calculation of the PCI, verifying that the pavement needs maintenance actions on the runway. Therefore, it is concluded that the applied methodology proved to be easy to use in the identification of pavement conditions, representing what was verified in the field. Finally, it is evident the need of the implementation of the management of pavements by the responsible public organs, contributing to minimize the traffic disturbances and wasted resources in palliative actions on the roads.
Monografia
Keywords: Pavimentos flexíveis; defeitos; índice de condição; caracterização; gerência de pavimentos; flexible pavements; defects; index condition; characterization; pavement management; ENGENHARIAS::ENGENHARIA CIVIL